2014
DOI: 10.1186/1471-2296-15-128
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of quality in primary health care: perspectives of patients and professionals based on focus group discussions

Abstract: BackgroundThe EUprimecare project-team assessed the perception of primary health care (PHC) professionals and patients on quality of organization of PHC systems in the participating countries: Estonia, Finland, Germany, Hungary, Italy, Lithuania and Spain. This article presents the aggregated opinions, expectations and priorities of patients and professionals along some main dimensions of quality in primary health care, such as access, equity, appropriateness and patient- centeredness.MethodsThe focus group te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 24 publications
1
99
0
3
Order By: Relevance
“…[21][22][23] In our experience, which is derived from several decades of work supporting health care quality improvement, 5 concepts can be used to describe what patients value: health, cure, healing, preconditions of health, and experience of care.…”
Section: Patient-centered Primary Care Value Frameworkmentioning
confidence: 99%
“…[21][22][23] In our experience, which is derived from several decades of work supporting health care quality improvement, 5 concepts can be used to describe what patients value: health, cure, healing, preconditions of health, and experience of care.…”
Section: Patient-centered Primary Care Value Frameworkmentioning
confidence: 99%
“…This paper revealed that young people"s experiences in this regard included perceived favouritism, perceptions that services offered in facilities were limited; as well as lack of confidence in treatment offered by the facilities. These findings are important against the background of evidence showing the importance of patient perception of health care quality in efforts to achieve more patient-centred health care systems and better health outcomes (Sofaer & Firminger, 2005;Papp et al, 2014). Studies from several sub-Saharan African countries have also shown that where young people report positive perceptions in relation to availability, acceptability and acceptability of health services, there tends to be use of health facilities and greater uptake of the services (Schriver et al, 2014).…”
Section: 3conclusion and Recommendationsmentioning
confidence: 90%
“…The rural or internal area patients have persistent barriers to having medical services because of the lack of suitable transport services, financial crisis, and profound knowledge in health care. As of this, providing better health service in rural areas had become a more significant challenge for local governments, as of now Italy is the only country that has implemented policies on rural area health issues [3]. Nevertheless, having communication with outlying areas is a big task to provide adequate medical support.…”
Section: Introductionmentioning
confidence: 99%